Access to oral & maxillofacial surgery in Sub-Saharan African countries - Fernando Garcia-Marin (Elsevier, 2021)
In many regions of Africa, and especially in rural areas, basic health services are scarce, access to general surgery very difficult and Oral and Maxillofacial Surgery non-existent. In these regions, patients with pathologies in the maxillofacial area, whether malformations, tumours, infections, trauma, etc., do not have the possibility of receiving any treatment, and the mortality rate from any of these pathologies is very high. Patients who survive with these maxillofacial pathologies will have to face all their lives, in addition to the limitations of their disease, the stigma of social marginalization linked to the obvious visibility of any facial deformity. Achieving universal access to surgery (including oral and craniomaxillofacial surgery) for all human beings is part of the Sustainable Development Goals set by the UN for 2030. Achieving these goals requires the cooperation of all: public and private sectors, academic institutions, professional associations, NGOs, international agencies, medical industry and the entire global Oral and Craniomaxillofacial surgery community.